Isolation of Campylobacter fetus subsp. jejuni from Human Fecal Specimens by Incubation at 35 and 42°C - Janssen, David (1982)
Campylobacter strains were isolated from human stool specimens that were cultured on modified Skirrow agar and incubated at 35 and 42°C. Incubation at 42°C resulted in more isolates, increased colony numbers, and earlier isolation than was found at 35°C.